Matrix Metalloproteinases 1 and 3 in Ovarian Cancer: Diagnostic and Prognostic Potential of Genetic Variants and Expression Profiling - Amal Mohamad Husein Mackawy; Hajed Obaid Alharbi; Ahmad Almatroudi; Wanian M. Alwanian; Khaled S. Allemailem (Diagnostics)
Background: Ovarian carcinoma (OC) is one of the foremost factors in female carcinoma-related fatalities worldwide. Matrix metalloproteinases (MMPs) are key mediators of tissue remodeling and are linked to tumor aggressiveness, yet there is still a lack of information on the link between genetic changes in MMPs-1,3 and the onset and progression of OC in Egyptian women. This study examines the effects of immunoreactive biomolecule variations of MMPs-1,3, as well as the MMP-1 (1607 1G/2G) and MMP-3 (-1171 5A/6A) genetic variants, on OC risk and progression in Egyptian women. Methods: Tissue specimens embedded in paraffin from 100 OC patients and 60 controls were stained using immunohistochemistry to examine expression of MMPs-1,3. MMP levels were quantified using ELISA, and single-nucleotide polymorphisms (SNPs) of MMPs-1,3 were genotyped using polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP). Results: Increased levels of MMPs-1,3 in OC patients relative to controls, with more of an increase in the late stages (III and IV) than in the early OC stages (I and II). Additionally, the MMP-1 2G/2G and MMP-3 6A/6A genotypes were more prevalent in OC patients than in controls. Ovarian MMPs-1,3 were comparatively elevated in the identified genotypes compared to the 1G/1G and 5A/5A genotypes, respectively. The transcriptional activity of MMPs-1,3 showed strong potential for distinguishing patients with epithelial ovarian carcinoma (EOC) from controls, boasting an area under the curve (AUC) of 0.956 and 0.816, respectively. Sensitivity and specificity were 94.0% and 90.0% for MMP-1 and 80.0% and 73.3% for MMP-3, respectively. Conclusions: The MMP-1 2G/2G and MMP-3 6A/6A genotypes are correlated with elevated MMP-1 and MMP-3 levels and immunohistochemical expression in carcinomatous ovarian tissues, particularly in advanced stages of OC. This indicates that genetic variations of MMPs-1,3 could be valuable diagnostic and prognostic markers for OC in Egyptian women. Our findings may carry clinical relevance for optimizing OC therapeutic effectiveness, contribute to the growing body of knowledge on the role of MMPs, and shed new light on the genetic background of OC. Future studies with larger sample sizes and comprehensive MMP genetic profiling are needed for results validation.